Socio-economic Security in the System of Transition to Sustainable Development of the Mining Region - Kudrevatykh Natalia; Slesarenko Ekaterina; Yilmaz Yigit (EDP Sciences, 2019)
The aim of the article is an assessment the socio-economic security of a mining region. The article describes the assessment socio-economic security of Kemerovo region by the technique that consists of economic and social components. Results of assessment showed a low level of socio-economic security of Kemerovo region. Majority of analyzed parameters in Kemerovo region has low indicators of socio-economic security. Indicators of assessment socio-economic security of Kemerovo region are at a level below then the average for the Siberian Federal district.
Keywords: Environmental sciences; GE1-350; 11. Sustainability; 12. Responsible consumption